Respuesta :

In both equations in the system, we know what y is equal to. Therefore, we can set the two equations equal to each other and solve for x.

-6(0.75)x = 4(x-1)

Simplify and distribute where needed.

-4.5x = 4x - 4

Combine like terms. We can subtract 4x to both sides to do so.

-8.5x = -4

Divide both sides by -8.5

x = 4/8.5 = 0.47059

Now plug x back into one of the equations and solve for y

4(0.47059 - 1) = -2.11765

So the answer is (0.47059, -2.11765)

This isn't one of the options so one of the equations may have been copied incorrectly. Hopefully this helps though!